Persistent Organic Pollutants Induced Protein Expression and Immunocrossreactivity by Stenotrophomonas maltophilia PM102: A Prospective Bioremediating Candidate. (26th June 2013) - Mukherjee, Piyali; Roy, Pranab
Abstract : A novel bacterium capable of growth on trichloroethylene as the sole carbon source was identified as Stenotrophomonas maltophilia PM102 by 16S rDNA sequencing (accession number of NCBI GenBank: JQ797560). In this paper, we report the growth pattern, TCE degradation, and total proteome of this bacterium in presence of various other carbon sources: toluene, phenol, glucose, chloroform, and benzene. TCE degradation was comparatively enhanced in presence of benzene. Densitometric analysis of the intracellular protein profile revealed four proteins of 78.6, 35.14, 26.2, and 20.47 kDa while the extracellular protein profile revealed two distinct bands at 14 kDa and 11 kDa that were induced by TCE, benzene, toluene, and chloroform but absent in the glucose lane. A rabbit was immunised with the total protein extracted from the bacteria grown in 0.2% TCE + 0.2% peptone. Antibody preadsorbed on proteins from peptone grown PM102 cells reacted with a single protein of 35.14 kDa (analysed by MALDI-TOF-mass-spectrometry) from TCE, benzene, toluene, or chloroform grown cells. No reaction was seen for proteins of PM102 grown with glucose. The PM102 strain was immobilised in calcium alginate beads, and TCE degradation by immobilised cells was almost double of that by free cells. The beads could be reused 8 times.